Comparison of arsenic and nitrate contaminations in shallow and deep aquifers of Kathmandu valley, Nepal - Gurung, Jaya Kumar; Ishiga, Hiroaki; Khadka, Mohan Singh; Shrestha, Nav Raj (Journal of Nepal Geological Society, 2007)
This study attempts to investigate arsenic and nitrate contaminations in the groundwater comprising about 45% of the total water supply in the Kathmandu valley. For this purpose, pH, electrical conductivity, oxidation-reduction potential, chemical oxygen demand, total arsenic, nitrate, total iron, and phosphate were analysed in sixty water samples. Shallow and deep (>200 m) aquifers of the valley depict contrasting groundwater chemistry. The ORP values of deep aquifers are relatively lower than those of shallow ones, indicating reducing conditions in the deeper zones. The shallow aquifers with high oxidation-reduction potential values (up to 272 mV) can be attributed to aerobic conditions and they also commonly contain elevated nitrate concentrations (up to 45 mg/l). On the other hand, arsenic contents are higher (>5 ?g/l) in the deep aquifers. Journal of Nepal Geological Society, 2006, Vol. 33 p.55-